Perception of youth towards causes, characteristics and ways to overcome premarital sex - Ling, Teck Keong (2013)
The purpose of this study was to investigate the perception of youth towards causes, characteristics and ways to overcome premarital sex among the youths of college and university in Johor Bahru area. One hundred and forty students from Southern University College completed the Causes and characteristics of premarital sex among youths questionnaire (CCPSAY). This study focuses on the causes of premarital sex and the ways to reduce or overcome this behaviour in teenager. The findings were analysed using the SPSS Version 16.0 (Statistical for the Social Sciences). This study showed 21.6% youth have premarital sex before. Most of youth percept that youth involve in premarital sex is because they feel exited and enjoy in it. Most of boy invite girl to have premarital sex. The best way to overcome the phenomenon of premarital sex in youth is the entire religious unit in Malaysia should deliver the messages of sex education and awareness of the risks and dangers of HIV/AIDS to teenager.